Positive Psychological Factors Are Associated With Better Spiritual Well-Being and Lower Distress in Individuals With Skin Diseases - Iani, Luca; Quinto, Rossella Mattea; Porcelli, Piero; Angeramo, Andrea-René; Schiralli, Andrea; Abeni, Damiano (Frontiers in Psychology, 2020)
In this study we examined whether aspects of positive functioning (reappraisal, sense of coherence [SOC], and positivity) were associated with spiritual well-being and psychological distress after controlling for negative functioning (skin-related symptoms, type of disease, and expressive suppression) in individuals with skin diseases. We also examined whether negative functioning aspects were linked to spiritual well-being and distress when controlling for aspects of positive functioning. The study used a cross-sectional design with a sample of 192 individuals with psoriasis and systemic sclerosis (Mage = 51.6 years, SD = 16.5). Two hierarchical multiple regressions were conducted to determine whether spiritual well-being and psychological distress were accounted for by skin-related symptoms, type of disease, emotion regulation strategies, SOC, and positivity. Positivity was the most important contributor to better spiritual well-being, followed by both the comprehensibility/manageability and meaningfulness SOC subscales, after controlling for the other variables. High skin-related symptoms and expressive suppression were associated with lower psychological distress, whereas high SOC and reappraisal correlated with higher psychological distress. The findings of this study pave the way for further research on how SOC and positivity may reduce the effects of both skin-related symptoms and emotion dysregulation and facilitate spiritual well-being of individuals with skin diseases. Interventions aimed to enhance inner resources of these individuals and help them to find a meaning in their experience of skin disease might reduce psychological distress and improve spiritual well-being. Our findings suggest that healthcare professionals should consider positive functioning aspects in future interventions for individuals with skin diseases.